Analisis Perkuatan Kolom Lingkaran Pada Bangunan Soft-Story Menggunakan Steel Jacketing Dengan Pendekatan 2D: Analysis Of Circular Column Strengthening In A Soft-Story Building Using Steel Jacketing With 2D Approach - Resmaindra, Muhammad Thariq; Mazaya, Bondan Dhifan; Apsari, Anindya Sulaksani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Collapse due to soft-story is often encountered in Indonesia. The collapse mechanism caused by soft stories is very dangerous, causing severe damage even collapse to the building structure. Steel jacketing is one of the means to strengthen the column which is considered effective in increasing the strength and stiffness of the reinforced elements hence soft story collapse in buildings can be prevented. The aim of this research is to evaluate the behavior of the existing building structure before strengthening the columns using limit analysis and pushover analysis and to determine the effect of strengthening columns with steel jacketing on the behavior and the performance of the structure. In this research, the existing structure is simulated to experience design errors and is modeled as a 2D portal with the function of a 4-story school building. From the results of the limit analysis, the existing structural model has the potential to experience a local collapse mechanism, followed by the potential for soft story collapse on the 1st floor. From the results of the pushover analysis, the existing structural model experiences the soft story mechanism and does not show performance points as required by FEMA 440. After carrying out this strengthening the column with steel jacketing, the structural model shows a better failure mechanism and the element performance obtained after strengthening is in the Immediate Occupancy (IO) range